Analisis Keamanan Aplikasi Mobile Denpasar Prama Sewaka - Adiriyanto, Shiennyta Florensia; Wibawa, I Gede Arta; Giri, Gst. Ayu Vida Mastrika (Jurnal Pengabdian Informatika, 2024)
Denpasar Prama Sewaka is a mobile application that integrates all the mobile applications owned by the Denpasar City Government. This mobile application is still in the development stage and, as such, it may have various security vulnerabilities that need to be addressed. This is typically due to the primary focus being on functionality and development rather than security. Mobile applications in the development phase tend to have common vulnerabilities that frequently occur, such as weak encryption, poor input validation, and insecurity related to network resources. Therefore, penetration testing of the Denpasar Prama Sewaka mobile application is essential to mitigate potential security risks. To prioritize the security of the code and manifest of this application, MobSF on Linux will be utilized to conduct the assessment.